ANATOMICAL CHARACTERIZATION OF THE BARK OF FIVE TREE SPECIES IN A NEOTROPICAL SAVANNA IN THE PERUVIAN AMAZON - Monteverde-Calderon, Enrique Gianlucca; Palacios-Ramos, Sonia Cesarina; Chavesta, Manuel (Floresta, 2025)
Tree bark fulfills vital functions such as protection against the environment, regulation of gas and water exchange, and adaptation to diverse conditions. Its ecological importance, especially in tropical forests, has been little explored, although recent studies have revealed its structural and functional diversity, highlighting its role in fire and drought resistance. Tree barks in dry tropical forests demonstrate adaptations, such as thickness, basic wood density, and anatomical characteristics that favor resistance to fire and water stress and allow the trees to survive extreme conditions. This study characterized the barks of five tree species common to the subxerophytic forests of Chanchamayo, Peru: Astronium fraxinifolium, Curatella americana, Luehea paniculata, Machaerium hirtum, and Physocalymma scaberrimum. The samples were collected in an ecosystem prone to fires and frequent water stress. Microscopic analyses identified the anatomical characteristics such as fibers, secretory tissues, and phloem. The results revealed that these species have developed diverse adaptive strategies, including the formation of rhytidome, sclerenchymatous tissue, and the arrangement of secretory canals to resist the environmental conditions dominating the Neotropical savannas. Additionally, the inner and outer bark thickness differences suggest variations in water storage and fire protection strategies.